Designing Android Based Game to Educate The Central Java Traditional Music Instrument for Children - Helarius Panji Aruna; Albertus Dwiyoga Widiantoro; Bernardinus Harnadi (Soegijapranata Catholic University, 2020)
This research was held to design create games that can provide children with knowledge of traditional musical instruments in Central Java.The initial design of the game is done by collecting data by interviewing the speakers. The game was created using Construct 2. This game has 5 different gameplay and when completing each stage you will get 3 traditional musical instruments except stage 5. Players can get information about traditional musical instruments and the sounds they produce. The game was tested on 41 respondents and the results of the game had a positive impact on players and provided new knowledge about traditional musical instruments.